2017
DOI: 10.1111/1556-4029.13664
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Morphine, Codeine, and Thebaine in Home‐Brewed Poppy Seed Tea by LCMS/MS

Abstract: Recently, medical examiners reported two cases of a 21-year-old male and 24-year-old male with high amounts of morphine in their blood at autopsy. It was suspected that the decedents ingested lethal amounts of morphine from home-brewed poppy seed tea. No studies to date have investigated opium alkaloid content extracted from poppy seeds by home-brewing methods. Various poppy seed products were purchased from online sources and extracted with four home-brewing methods representative of recipes found on drug use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 16 publications
3
44
1
Order By: Relevance
“…The morphine, codeine, and thebaine content in poppy seed tea was analyzed by liquid chromatography-tandem mass spectrometry and found a morphine concentration of < 1–2788 mg/kg, a codeine concentration of < 1–247.6 mg/kg, and a thebaine concentration of < 1–124 mg/kg with alkaloid yields varying depending on extraction method. This suggests that high, potentially lethal doses of morphine can be found in poppy seed tea [5].…”
Section: Drug Concentrationsmentioning
confidence: 99%
“…The morphine, codeine, and thebaine content in poppy seed tea was analyzed by liquid chromatography-tandem mass spectrometry and found a morphine concentration of < 1–2788 mg/kg, a codeine concentration of < 1–247.6 mg/kg, and a thebaine concentration of < 1–124 mg/kg with alkaloid yields varying depending on extraction method. This suggests that high, potentially lethal doses of morphine can be found in poppy seed tea [5].…”
Section: Drug Concentrationsmentioning
confidence: 99%
“…One report analyzed multiple different preparations and measured a concentration of morphine in the range of 10-105 mg/kg of poppy seeds and a concentration of codeine in the range of 3.1-11.2 mg/kg of poppy seeds [11]. Another report found that potentially lethal amounts of morphine can be produced with home preparation of poppy seed tea with a range of < 1-2,788 mg/kg [7]. Of note, the brand of seeds used by this patient produced the highest concentrations of morphine in poppy seed tea brewed in a prior report [7].…”
Section: Discussionmentioning
confidence: 99%
“…Another report found that potentially lethal amounts of morphine can be produced with home preparation of poppy seed tea with a range of <1–2,788 mg/kg [7]. Of note, the brand of seeds used by this patient produced the highest concentrations of morphine in poppy seed tea brewed in a prior report [7]. Numerous case reports have echoed this concern regarding the potential lethality of ingesting the products of these unwashed seeds [12-15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Carlin et al analyzed seeds scraped from the top of the finished baked product, it is plausible that the reported loss of alkaloids might be due to transfer of alkaloids from the surface of the seeds to the batter. Opium alkaloids in poppy seeds can be significantly reduced by washing the surface of the seeds, but lack of reported recovery experiments by the authors leave unanswered whether losses are "true losses" due to degradation of the alkaloid compounds, or are an artifact of the compounds simply transferring to the batter (CONTAM Panel et al, 2018;Powers et al, 2018;Shetge et al, 2020). We hypothesize that follow-up experiments taking into account recovery may find higher alkaloid concentrations in the baked product than initially reported.…”
mentioning
confidence: 86%